New evidence between cost of debt and information disclosure level - Quang, Le Vinh; Luc, Pham Tan Luc; Thuan, Tran Trung (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2025)
This study examines the factors that influence the cost of debt (CoD) among companies listed on the Vietnamese stock market, with a particular focus on the level of information disclosure and financial distress prediction indicators. The samples consist of companies included in the VN100 index, which represents the top 100 largest and most liquid stocks in Vietnam. Data was collected from audited financial statements and annual reports published between 2019 and 2023. The study employs multiple regression analysis to explore the relationship between CoD and various explanatory variables, including firm-specific characteristics (such as firm size, profitability, and governance structures), financial distress indicators (e.g Altman z-score), and the level of information disclosure. The findings indicate a statistically significant correlation between the level of information disclosure, financial distress prediction indicators, and the CoD. Specifically, the results reveal that companies with higher levels of information disclosure tend to face higher debt costs. The counterintuitive outcome suggests that firms may disclosure more detailed information when they are under financial stress or attempting to signal transparency to mitigate lender concerns, which in turn may rise the perceived risk among creditors.